1996
DOI: 10.1007/bf00227266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gestational or neonatal treatment with alpha-difluoromethylornithine on ornithine decarboxylase and polyamines in developing rat brain and on adult rat neurochemistry

Abstract: Pregnant rats were treated for five consecutive days during gestation with s.c. injections of the ornithine decarboxylase (ODC) inhibitor alpha-difluoromethylornithine (DFMO). Treatment beginning at gestational days 13 or 14 was effective in inhibiting ODC and altering polyamine levels, and resulted in relatively small decreases in body and forebrain weight, but not in significant differences in adult neurochemistry. Neonatal rats were treated with DFMO from postnatal day 0 (PD 0) to PD 24. In addition to some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…Once neuronal cells have matured and proliferation has ceased, polyamine levels drop. We recognize that there is considerable data available showing that DFMO depletes polyamine levels (4244). However, it was not the objective of this study to do an in-depth investigation into whether the observed differences in cognition were directly attributed to alerted levels of polyamines.…”
Section: Discussionmentioning
confidence: 98%
“…Once neuronal cells have matured and proliferation has ceased, polyamine levels drop. We recognize that there is considerable data available showing that DFMO depletes polyamine levels (4244). However, it was not the objective of this study to do an in-depth investigation into whether the observed differences in cognition were directly attributed to alerted levels of polyamines.…”
Section: Discussionmentioning
confidence: 98%
“…This dose has also been shown to reduce the severity of EtOH withdrawal behaviors (Davidson and Wilce, 1998). DFMO was administered only on a single day because of concern regarding the important role that polyamines play in CNS development and because repeated injections of DFMO itself can cause reductions in cerebellar size (Schweitzer et al, 1989; Sparapani et al, 1996). This resulted in six treatments groups: Intubated Control/Saline, Intubated Control/DFMO, Intubated EtOH /Saline, Intubated EtOH /DFMO and Non-intubated Control/Saline and Non-intubated Control/ DFMO.…”
Section: - Materials and Methodsmentioning
confidence: 99%
“…The present study represented a proof of concept study to determine if DFMO would modify the behavioral consequences of single insults or RCI. Considerable data are available showing that DFMO depletes PA levels [37][39], but for this study we focused exclusively on how DFMO affects factors associated with cognition.…”
Section: Introductionmentioning
confidence: 99%